واقع اهتمامات الأنثروبولوجياالتطبيقيةفي الدراسات العربية - خواني, خالد (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
Appliedanthropologyisinterested to applyitsknowledge, itsmethods and theoreticalanthropology to solve social problems. This studyaims to highlight the importance of Arabanthropology in the development of society and the need for itspresence in all areas of knowledge and expertise that affect society. The main areas thatcouldbenefitfromappliedanthropologicalstudies are the cultural sector, community service, health and planning of developmentprojectsthat respect the nature of society, social laws in  accordance with the culture and system proposal of the community. The studyquotedsomeArabanthropologicalstudy in applied vision.